FOUNDATIONS OF SUSTAINABLE ECONOMIC DEVELOPMENT AND THEIR ROLE IN REGIONAL POVERTY REDUCTION: THEORY AND PRACTICE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the theoretical foundations and practical approaches to poverty reduction in regions within the context of modern socioeconomic realities. Special attention is given to the analysis of existing models of sustainable economic development that contribute to addressing poverty issues. The authors propose viewing poverty not only as a social problem but also as an economic challenge requiring a comprehensive approach. Recommendations are presented for implementing effective strategies that can be adapted to various regions, taking into account their specific characteristics. The focus is on combining theoretical concepts and practical measures aimed at the long-term reduction of poverty levels.
Keywords: poverty reduction, regional economy, sustainable development, socio-economic development, poverty models, poverty reduction strategies